Jak „czytać” dzieło sztuki plastycznej? - Steliga, Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
Education through art is one of the most important and necessary forms of knowledge and human experience. A work of art is a result of the creator’s artistic activity, an objectification of his design and it includes a series of activities. This article discusses the core curriculum for the subject of fine arts, the basic categories of fine arts’ works, and also presents examples of analyses of painting artworks.
Keywords: a work of art; education through art; analysis of painting artworks